2021
DOI: 10.1051/0004-6361/202038603
|View full text |Cite
|
Sign up to set email alerts
|

Physically motivated heat-conduction treatment in simulations of solar-like stars: effects on dynamo transitions

Abstract: Context. Results from global magnetoconvection simulations of solar-like stars are at odds with observations in many respects: They show a surplus of energy in the kinetic power spectrum at large scales, anti-solar differential rotation profiles, with accelerated poles and a slow equator, for the solar rotation rate, and a transition from axi-to non-axisymmetric dynamos at a much lower rotation rate than what is observed. Even though the simulations reproduce the observed active longitudes in fast rotators, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Several numerical studies have shown that the deep parts of density-stratified CZs are often weakly stably stratified (e.g., Chan & Gigas 1992;Tremblay et al 2015;Bekki et al 2017;Hotta 2017;Käpylä et al 2017). Such layers have also been found from semi-global and global simulations of rotating solar-like CZs (e.g., Karak et al 2018;Käpylä et al 2019;Viviani & Käpylä 2021) as well as from fully convective spheres (Käpylä 2021). We call this layer the Deardorff zone after Brandenburg (2016).…”
Section: Overshooting Below the Convection Zonementioning
confidence: 57%
“…Several numerical studies have shown that the deep parts of density-stratified CZs are often weakly stably stratified (e.g., Chan & Gigas 1992;Tremblay et al 2015;Bekki et al 2017;Hotta 2017;Käpylä et al 2017). Such layers have also been found from semi-global and global simulations of rotating solar-like CZs (e.g., Karak et al 2018;Käpylä et al 2019;Viviani & Käpylä 2021) as well as from fully convective spheres (Käpylä 2021). We call this layer the Deardorff zone after Brandenburg (2016).…”
Section: Overshooting Below the Convection Zonementioning
confidence: 57%
“…Käpylä et al 2017;Käpylä 2019Käpylä , 2021. Thus far these studies have mostly concentrated on non-rotating convection (see, however Käpylä et al 2019;Viviani & Käpylä 2021). Here rotation is included to study its impact on the formation and extent of stably stratified Deardorff layers where the convective flux runs counter to the entropy gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Such layers have also been found from semi-global and global simulations of rotating solarlike CZs (e.g. Karak et al 2018;Käpylä et al 2019;Viviani & Käpylä 2021) as well as from fully convective spheres (Käpylä 2021). We call this layer the Deardorff zone after Brandenburg (2016).…”
Section: Overshooting Below the Convection Zonementioning
confidence: 63%